The Use of Mind Mapping In Generating Students’ Idea - Fauziah, Ula Nisa El (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2017)
Writing is considered as the hardest skill to be learned. Some students said that the difficult part to write is to generate ideas. They admitted that their ideas were out of focus. They could not generate and develop the ideas. To solve it, teachers surely require various teaching techniques that help students to generate ideas in writing. One of the technique is mind mapping. Based on this mentioned reasons, this study is aimed to investigate the differences between teaching writing that does not use mind mapping and the one that uses it in term of ideas.This study employed qualitative method. The data sources of this study were first grade students in one of departement in university at Bandung. The collected data were obtained by writing tests. The result of writing tests was scored by using a rubric. Based on the analysis result, it was found that there were the differences in the writing that did not use mind mapping and the one that used it in term of ideas. The writing that used mind mapping tended to be more focus. Besides, it also had deepen explanation of the topic as well as clear main idea and supporting ideas. From this finding, it can be inffered that mind mapping do really help students to generate ideas in writing. Therefore, teachers can use this technique to teach writing in the classroom. Keywords: writing, mind mapping, main idea